Publishing & Supporting the Academic - Hammond, Craig Andrew; Allan, David; Enriquez, Judith (PRISM: Casting New Light on Learning, Theory and Practice, 2024)
Editorial for the General Issue 6 (number 1) 2024, entitled ' Publishing & the Supporting the Academic'; written by David Allan, Judith Enrioquez, and Craig Hammond